Phthalate metabolites in obese individuals undergoing weight loss: Urinary levels and estimation of the phthalates daily intake - Alin C. Dirtu; Tinne Geens; Eveline Dirinck; Govindan Malarvannan; Hugo Neels; Luc Van Gaal; Philippe G. Jorens; Adrian Covaci (Environment International, 2013)
Human exposure to chemicals commonly encountered in our environment, like phthalates, is routinely assessed through urinary measurement of their metabolites. A particular attention is given to the specific population groups, such as obese, for which the dietary intake of environmental chemicals is higher. To evaluate the exposure to phthalates, nine phthalate metabolites (PMs) were analyzed in urine collected from obese individuals and a control population. Obese individuals lost weight through either bariatric surgery or a conservative weight loss program with dietary and lifestyle counseling. Urine samples were also collected from the obese individuals after 3, 6 and 12 months of weight loss. Individual daily intakes of the corresponding phthalate diesters were estimated based on the urinary PM concentrations. A high variability was recorded for the levels of each PM in both obese and control urine samples showing the exposure to high levels of PMs in specific subgroups. The most important PM metabolite as percentage contribution to the total PM levels was mono-ethyl phthalate followed by the metabolites of di-butyl phthalate and di 2-ethyl-hexyl phthalate (DEHP). No differences in the PM levels and profiles between obese entering the program and controls were observed. Although paralleled by a significant decrease of their weight, an increase in the urinary PM levels after 3 to 6 months loss was seen. Constant figures for the estimated phthalates daily intake were observed over the studied period, suggesting that besides food consumption, other human exposure sources to phthalates (e.g. air, dust) might be also important. The weight loss treatment method followed by obese individuals influenced the correlations between PM levels, suggesting a change of the intake sources with time. Except for few gender differences recorded between the urinary DEHP metabolites correlations, no other differences were observed for the urinary PM levels as a function of age, body mass index or waist circumference. Linear regression analysis showed almost no significance of the relationship between measured urinary PMs and serum free thyroxine, thyroid-stimulating hormone (TSH) for all obese individuals participating to the study, while for the control samples, several PMs were significantly associated with the serum TSH levels. Keywords: Intake estimation, Phthalates, Phthalate metabolites, Obesity, Urine, Weight loss